2013
DOI: 10.5901/mjss.2013.v4n6p593
|View full text |Cite
|
Sign up to set email alerts
|

Health Sector Reforms: Implications for Maternal and Child Healthcare in South Africa

Abstract: Generally, public health facilities in developing countries tend to be underfunded and inefficient. In South

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Many studies in Africa have indicated the need for primary health care (PHC) reform, not merely to transform the health system but also to ensure a better life for all. 4 Reforms include changes in financing, privatisation, decentralisation, integration of service delivery, and improvement of efficiency, equity and effectiveness of the health sector in general. 4 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies in Africa have indicated the need for primary health care (PHC) reform, not merely to transform the health system but also to ensure a better life for all. 4 Reforms include changes in financing, privatisation, decentralisation, integration of service delivery, and improvement of efficiency, equity and effectiveness of the health sector in general. 4 …”
Section: Introductionmentioning
confidence: 99%
“… 4 Reforms include changes in financing, privatisation, decentralisation, integration of service delivery, and improvement of efficiency, equity and effectiveness of the health sector in general. 4 …”
Section: Introductionmentioning
confidence: 99%